2013
DOI: 10.3748/wjg.v19.i23.3665
|View full text |Cite
|
Sign up to set email alerts
|

Double-balloon enteroscopy in small bowel tumors: A Chinese single-center study

Abstract: DBE is a useful diagnostic tool with high clinical practice value and should be considered the gold standard for the investigation of small bowel tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 24 publications
2
36
2
3
Order By: Relevance
“…Of the 25 patients with an age range from 34-to 70-year-old (mean: 54 ± 12 years), 8 were male and 17 were female. Obscure gastrointestinal bleeding, including tarry or bloody stool and intermittent melena, was observed in all cases, and one case also involved hematemesis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 25 patients with an age range from 34-to 70-year-old (mean: 54 ± 12 years), 8 were male and 17 were female. Obscure gastrointestinal bleeding, including tarry or bloody stool and intermittent melena, was observed in all cases, and one case also involved hematemesis.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of specific clinical manifestations and the location of the tumors make the diagnosis difficult. Routine diagnostic imaging modalities mainly consist of endoscopic examination, computed tomography (CT) scanning, and magnetic resonance imaging (MRI) [7][8][9][10][11][12] . However, doctors who admit patients with acute or subacute obscure gastrointestinal bleeding (OGIB) prefer to conduct emergency interventional digital subtraction angiography (DSA), whereas some routine exams are not able to identify the bleeding [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While data from Japan multicentre study in patient underwent DBE showed that lymphomas and GIST were the most common small bowel tumour 5 . The result from single centre Chinese study from 78 patients with small bowel tumour shows adenocarcinoma was the most common tumour, followed by lymphoma and GIST 6 . From our case series (Table 1) we found most of the tumours were gastrointestinal stromal tumor.…”
Section: Discussionmentioning
confidence: 99%